Use of a modified angioplasty balloon catheter in the dilatation of tight biliary strictures. Issue 5 (May 1990) - Rao, K J; Blake, H; Theodossi, A
Abstract : Nineteen biliary strictures were dilated using a modified angioplasty balloon catheter to allow insertion of a 10F prosthesis. In each instance biliary strictures were successfully dilated which had previously been too tight to widen with standard endoscopic biliary dilating catheters. Eleven patients had malignant hilar strictures, four malignant distal common bile duct strictures, and four benign strictures. There were no complications as a result of the procedure and satisfactory biliary drainage was established in all patients. We conclude that tight biliary strictures can be successfully dilated using a modified angioplasty balloon catheter.